Tools of titans : the tactics, routines, and habits of billionaires, icons, and world-class performers / Timothy Ferriss. - Ferriss, Timothy (Vermilion, 2016)
For the last two years, Timothy Ferriss has interviewed nearly 200 world-class performers for his podcast, 'The Tim Ferriss Show'. The guests range from super celebs and athletes to legendary Special Operations commanders and black-market biochemists. For most of the guests, it's the first time they've agreed to a 2-3 hour interview, and the show is on the cusp of passing 100 million downloads. This book contains the distilled tools, tactics, and 'inside baseball' you won't find anywhere else. It also includes new tips from past guests, and life lessons from new 'guests' you haven't met.